Massively Multiplayer Online Games Industry: A Review and Comparison From Middleware to Publishing - Sim, Boon Seong (2007)
Our team was engaged with Monumental Games to undertake an internship project to study and analyse the Massively Multiplayer Online Games industry (Middleware, game development and publishing industry)